2021
DOI: 10.3390/jcs5030074
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Solution for Static and Dynamic Analysis of Graphene-Based Hybrid Flexoelectric Nanostructures

Abstract: Owing to their applications in devices such as in electromechanical sensors, actuators and nanogenerators, the consideration of size-dependent properties in the electromechanical response of composites is of great importance. In this study, a closed-form solution based on the linear piezoelectricity, Kirchhoff’s plate theory and Navier’s solution was developed, to envisage the electromechanical behaviors of hybrid graphene-reinforced piezoelectric composite (GRPC) plates, considering the flexoelectric effect. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…The deflection continues to decrease as the flexoelectric coefficient increases in magnitude. We observe the same trend of results in published literature (Shingare and Naskar, 2021c) which affirms the validity of our present model (EKM) further. In addition to this, in all three distributions, there exists a significant reduction in the magnitude of deflection in between f 14 = 10 −6 C/m and f 14 = 10 −8 C/m whereas after f 14 = 10 −8 C/m, this reduction is almost negligible.…”
Section: Elastic and Geometrical Propertiessupporting
confidence: 92%
See 3 more Smart Citations
“…The deflection continues to decrease as the flexoelectric coefficient increases in magnitude. We observe the same trend of results in published literature (Shingare and Naskar, 2021c) which affirms the validity of our present model (EKM) further. In addition to this, in all three distributions, there exists a significant reduction in the magnitude of deflection in between f 14 = 10 −6 C/m and f 14 = 10 −8 C/m whereas after f 14 = 10 −8 C/m, this reduction is almost negligible.…”
Section: Elastic and Geometrical Propertiessupporting
confidence: 92%
“…8. From figures 7 and 8, it can be observed that the results obtained from EKM and Ritz solutions are found to be in excellent agreement with the results estimated by Shingare and Naskar (2021c). Concerning the issue of non-linearity mentioned in previous Section 2.5.1, these figures also clearly indicate that the effect of neglecting non-linear terms is acceptable even in flexoelectric cases (f 14 ≠ 0).…”
Section: Priori Functionsupporting
confidence: 78%
See 2 more Smart Citations
“…A piezoelectric micro/nanoscale structure such as beams, plates, rods, and panels is found to be having massive capabilities for numerous applications including energy harvesters which contain sensors, actuators, parallel plate capacitors, and nanogenerators. 310 Nanoscale beams and rods are extensively used in several NEMS applications. Precisely from the past couple of years, piezoelectric/non-piezoelectric materials have fascinated great interest for producing energy harvesters to generate the electric response on the application of mechanical load to the structure.…”
Section: Introductionmentioning
confidence: 99%